2021
DOI: 10.31234/osf.io/v56wz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social cognitive processes explain bias in juror decisions

Abstract: Jury decisions are among the most consequential social decisions in which bias plays a notable role. While courts take a number of measures to reduce the influence of bias on decisions about case strength or deserved punishment based on evidence introduced during a trial, jurors may still incorporate personal biases based on knowledge, experience, emotion, and beliefs independent of evidence. One common form of this bias, crime-type bias, is the extent to which the perceived strength of a case depends on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 67 publications
0
4
1
Order By: Relevance
“…Elsewhere, we found that brain activation patterns associated with scenario effects on case strength are distinct from the patterns described here for evidence accumulation (Castrellon et al, 2021). These scenario effects were associated with brain regions related to social cognition.…”
Section: Resultscontrasting
confidence: 70%
See 4 more Smart Citations
“…Elsewhere, we found that brain activation patterns associated with scenario effects on case strength are distinct from the patterns described here for evidence accumulation (Castrellon et al, 2021). These scenario effects were associated with brain regions related to social cognition.…”
Section: Resultscontrasting
confidence: 70%
“…Since this model has the advantage of accounting for sparsely sampled data, we can estimate effects for all scenarios even though participants did not view all possible combinations of scenarios and evidence types. We previously applied this model to a large online sample of participants (Pearson et al, 2018) and show here that the model generally replicates case strength and punishment effects (Castrellon et al, 2021).…”
Section: Computational Modelingmentioning
confidence: 77%
See 3 more Smart Citations